Groundwater Flow Modeling of a Near-Surface Disposal Repository for Low- and Intermediate-Level Radioactive Waste in Southwest China - Zhang, Huang; Zhang, Qiulan; Chen, Yunli; Shao, Jingli; Cui, Yali; Wan, Wenyi; Han, Shangqi (Frontiers in Environmental Science, 2022)
The influence and function of engineering facilities were increasingly concerned about the safety analysis of Low and Intermediate Level Radioactive Waste (LILW). In terms of near-surface disposal, many artificial facilities were set down, such as drainage facilities, covering layers, and disposal units. To analyze the long-term impact of these artificial facilities on groundwater in the disposal site area, we built four time-continuing models by setting the time nodes of parameter or boundary changes using FEFLOW code, considering the possible aging and degradation state of these facilities. According to the models, the site area's groundwater level situations for long-term safety assessment were predicted. The results showed the different regulating abilities of drainage facilities affected the groundwater level of the disposal site in different degradation states, which also reflected the necessity of artificial facilities simulation in groundwater modeling. Besides, the Monte Carlo method and surrogate model were adopted to analyze the influence of the uncertainty of model parameters on the output of groundwater flow models. This study could give further understanding of groundwater flow modeling for long-term safety assessment of near-surface disposal engineering.